THE EFFECTIVENESS OF RELIGIOUS EXTRACURRICULAR ACTIVITIES IN IMPROVING STUDENTS' PRACTICE OF ISLAMIC TEACHINGS IN MADRASAH - Karlina, Lilis (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to determine the effectiveness of religious extracurricular activities in increasing students' practice of Islamic teachings at MA Negeri 1 Probolinggo. This research uses a qualitative method with a case study type. The research subjects were students of MA Negeri 1 Probolinggo who took part in religious extracurricular activities. Data was collected through interviews, observation and documentation. The research results show that religious extracurricular activities at MA Negeri 1 Probolinggo are effective in increasing students' practice of Islamic teachings. This is demonstrated by increasing students' knowledge, attitudes and skills in practicing Islamic teachings. Increased student knowledge is demonstrated by students' ability to explain and understand Islamic teachings. Improving student attitudes is shown by increasing student awareness to implement Islamic teachings in everyday life. Increasing student skills is demonstrated by students' ability to apply Islamic teachings in everyday life.